Experimental and Theoretical Core Level and Valence Band Analysis of Clean Perovskite Single Crystal Surfaces. Issue 13 (5th February 2022) - García‐Fernández, Alberto; Svanström, Sebastian; Sterling, Cody M.; Gangan, Abhijeet; Erbing, Axel; Kamal, Chinnathambi; Sloboda, Tamara; Kammlander, Birgit; Man, Gabriel J.; Rensmo, Håkan; Odelius, Michael; Cappel, Ute B.
Abstract: A detailed understanding of the surface and interface properties of lead halide perovskites is of interest for several applications, in which these materials may be used. To develop this understanding, the study of clean crystalline surfaces can be an important stepping stone. In this work, the surface properties and electronic structure of two different perovskite single crystal compositions (MAPbI3 and Cs x FA1– x PbI3 ) are investigated using synchrotron‐based soft X‐ray photoelectron spectroscopy (PES), molecular dynamics simulations, and density functional theory. The use of synchrotron‐based soft X‐ray PES enables high surface sensitivity and nondestructive depth‐profiling. Core level and valence band spectra of the single crystals are presented. The authors find two carbon 1s contributions at the surface of MAPbI3 and assign these to MA + ions in an MAI‐terminated surface and to MA + ions below the surface. It is estimated that the surface is predominantly MAI‐terminated but up to 30% of the surface can be PbI2 ‐terminated. The results presented here can serve as reference spectra for photoelectron spectroscopy investigations of technologically relevant polycrystalline thin films, and the findings can be utilized to further optimize the design of device interfaces. Abstract : The surface properties and electronic structure of two perovskite single crystals (MAPbI3 and Cs x FA1– x PbI3 ) are investigated using synchrotron‐based soft X‐ray photoelectron spectroscopy, molecular dynamics simulations, and density functional theory. Core level and valence band spectra are presented, providing reference values for future investigations. Moreover, two carbon 1s contributions from methylammonium ions at the surface of MAPbI3 can be distinguished.